Role Of Organizational Context On Digital Librarys Success Factor. - Dahlan, Noornina; Karia, Noorliza; Asaari, Muhammad Hasmi Abu Hassan; Ramayah, T.; Goon, Tuck Lee (USM, 2006)
Organizational context was examined on postgraduate students on their perception on ease of use and the impact in relation to digital library.